Czerwone gitary. (Gdynia : [wydawca nieznany], 1967)
Afisz informujący o koncertach w Gdańsku 19-22.04.1967 r.
Keywords: Czerwone Gitary; Życie muzyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Nowy Port (Gdańsk, Polska ; dzielnica) -- 1945-1970 -- druki ulotne; Orunia-Św. Wojciech-Lipce (Gdańsk, Polska ; dzielnica) -- druki ulotne